(untitled) (American Journal of Islam and Society, 2009)
The present American moment has been hailed by some as inaugurating an era of “post-black” politics with the candidacy and election of President Barack Obama. Obama’s election, in the words of Manning Marable, indicates the possibility that America has entered “an age of post-racial politics, in which leadership and major public policy debates would not be distorted by factors of race and ethnicity” (“Racializing Obama: The Enigma of Post-Black Politics and Leadership,” Souls 11, no. 1 [2009]: 1-15). While his campaign and victory heralded the message of hope in a “post-racial” landscape, the dangers of stumbling blindly onto the bandwagon could, and in some cases have, result(ed) in erasing race’s enduring presence in contemporaryAmerican politics. Thus, there is perhaps no better time for the publication of Race and Arab Americans Before and After 9/11, as it counters contemporary public amnesia by reminding us that race and inequality still permeate the lives of minority populations. Speaking to an interdisciplinary audience and seeking to fill a critical gap in the field ofAmerican racial and ethnic studies, this collection of essays highlights the complex and slippery ways in which race permeatesArab andArab-American engagements with the American social hierarchy. Foregrounding the complexities of Arab-American racial formation as a critical site of inquiry in the introduction, Nadine Naber calls for moving beyond the usual liberal multiculturalist “add on” approach in order to consider “the shifting and contradictory historical contexts through whichArabAmericans have engaged with immigration, assimilation, and racialization” (p. 4). In a concise but evocative historical précis, she shows how “anti-Arab racism represents a recurring process of the construction of the Other within U.S. liberal politics in which long-term trends of racial exclusion become intensifiedwithinmoments of crisis in the body politic…” (p. 31) ...